Discursive Resistance and Agency in Indonesian Courtrooms: Linguistic and Prosodic Strategies of Negotiating Power in Coercive Questioning - Arum Priadi (Journal of English Language and Education, 2025)
This study investigates how witnesses in Indonesian criminal courts exercise agency and resist coercive questioning through linguistic and prosodic strategies. Challenging the perception of witnesses as passive participants, it examines how they negotiate institutional power and redefine authority in talk. Guided by the research question—how do witnesses use linguistic and prosodic cues to assert agency under coercive questioning? —the study employs Critical Discourse Analysis informed by Foucault’s notion of power/knowledge and Goffman’s theory of face-work. Data comprise 18 hours of cross-examination from three district courts, analyzed using AntConc and ELAN to integrate corpus-assisted and prosodic perspectives. Findings reveal four resistance strategies: assertive repair, strategic evasion, hedging, and tonal dissent, demonstrating that resistance is patterned and interactionally embedded. These strategies transform compliance into controlled agency, revealing how witnesses reclaim epistemic authority within institutional discourse. The study contributes to Critical Discourse Analysis and forensic linguistics by integrating prosodic and corpus-based tools to conceptualize resistance as both linguistic and embodied practice.